2019
DOI: 10.2147/ijwh.s194262
|View full text |Cite
|
Sign up to set email alerts
|

<p>Curcumin and endometrial carcinoma: an old spice as a novel agent</p>

Abstract: One of the clinically major gynecological cancers is endometrial carcinoma that develops from the lining of the uterus. During the past years, different approaches have been developed to treat endometrial carcinoma, among which natural herbal medicine has recently faired as an effective method. The yellow Indian spice known as curcumin has been extolled for its healing powers and has recently been adopted for investigation by the scientific community as a potent anti-cancerous agent. This review focuses on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…Eventhough curcumin is a promising drug for mono or combination therapy for endometrial cancer, it is still not enough research in human. Research cautiously extrapolate results from experiments which were done either in vitro or in vivo in rodents, zebrafish and human beings drawn the conclusions curcumin has a significant effect on endometrial carcinoma where it exhibited pro-apoptotic, anti-proliferative, and anti-migratory activities of endometrial tumor cells [1], [2][6] [19] [21]. In this clinical case we could not prove with pathways of curcumin treatment lead to increase the patient survival rate dramatically for more than two years and prolong relapse of endometrial cancer for more than one year.…”
Section: Advances In Health Sciences Research Volume 22mentioning
confidence: 99%
See 3 more Smart Citations
“…Eventhough curcumin is a promising drug for mono or combination therapy for endometrial cancer, it is still not enough research in human. Research cautiously extrapolate results from experiments which were done either in vitro or in vivo in rodents, zebrafish and human beings drawn the conclusions curcumin has a significant effect on endometrial carcinoma where it exhibited pro-apoptotic, anti-proliferative, and anti-migratory activities of endometrial tumor cells [1], [2][6] [19] [21]. In this clinical case we could not prove with pathways of curcumin treatment lead to increase the patient survival rate dramatically for more than two years and prolong relapse of endometrial cancer for more than one year.…”
Section: Advances In Health Sciences Research Volume 22mentioning
confidence: 99%
“…Endometrial cancer (EC) is a group of epithelial malignancies that occurs in the endometrium of perimenopausal or postmenopausal women [1]. In the US alone, uterine cancer is the fourth most diagnosed type of cancer in women [2]. Data from Indonesian Academic Hospital in the year 2007 showed that uterine cancer is the third most diagnosis gynecology type of cancer after cervical cancer and ovarian cancer [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Curcumin (Cur), a hydrophobic polyphenol compound extracted from the rhizome of Curcuma longa L., has exhibited extensive anti-tumor potential in a wide range of cancer, such as breast, colon, colorectal, pancreatic, prostate, esophageal, head and neck cancers, endometrial carcinoma, and glioblastoma multiforme (El Khoury et al., 2019; Forouzanfar et al., 2019; Karavasili et al., 2019; Komal et al., 2019; Shahcheraghi et al., 2019; Yeung et al., 2019). Moreover, Cur can inhibit the invasion and metastasis of various cancers (Li & Zhang, 2014; Shafabakhsh et al., 2019; Wang et al., 2019).…”
Section: Introductionmentioning
confidence: 99%